2017
DOI: 10.1016/j.jtho.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Institutional Prospective Study of Reirradiation with Proton Beam Radiotherapy for Locoregionally Recurrent Non–Small Cell Lung Cancer

Abstract: In this prospective study, PRT for recurrent NSCLC is feasible but can be associated with significant toxicity. Providers should remain cautious in reirradiating NSCLC, paying close consideration to tumor volume, location, and relevant dosimetric parameters. Further research is needed for optimal patient selection to improve overall outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 40 publications
2
81
0
Order By: Relevance
“…Proton beam therapy for reRT has been investigated at other disease sites including head and neck, 38,39 central nervous system, 40,41 lung, 42,43 gynecological, 44 and gastrointestinal malignancies. [45][46][47] A recent systematic review found that reRT with PBT is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Proton beam therapy for reRT has been investigated at other disease sites including head and neck, 38,39 central nervous system, 40,41 lung, 42,43 gynecological, 44 and gastrointestinal malignancies. [45][46][47] A recent systematic review found that reRT with PBT is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the simple tracking method was valuable for improving GTV coverage. The practicalities and limitations of tracking and gating techniques in IMPT have also been reported by the group at Paul Scherrer Institute 41,42 Another key aspect is plan robustness, meaning the susceptibility of the nominal treatment plan due to uncertainties (e.g., setup uncertainties) or motion. Some treatment planning systems already allow the evaluation of plan robustness.…”
Section: Proton Therapy Techniques and Considerations For Treatment Pmentioning
confidence: 86%
“…In a phase II clinical trial with sorafenib monotherapy for 57 pre-treated Stage IIIB-IV NSCLC patients with a KRAS mutation, a partial response occurred more frequently in the five patients using metformin during treatment compared with the non-users (p=0.01) 41 . Groenendijk et al 42 recently published a post hoc analysis on that study, reporting that six weeks after treatment with sorafenib, all patients using metformin had either a partial response or stable disease, while 27 of the patients not using metformin had progressive disease (p=0.01). Taking these findings from bed to benchside, the authors treated NSCLC cell lines and mouse NSCLC-xenograft tumours with sorafenib and metformin (monotherapy or in combination) and found an anti-proliferative effect in the NSCLC cell lines and a lower mean tumour volume in the xenografts treated with the drug combination compared to sorafenib monotherapy (p=0.046).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations